(untitled) (Biological Sciences - PJSIR, 2005)
The chromate coating on zinc-aluminum deposits has been studied. Zinc-aluminum deposition from non- cyanide bath was carried out at current density 3-3.5 A/dm2, plating voltage 1.25 V, temperature 18-20 oC, for 15 min. The effect of aluminum chloride on the rest potentials of golden, colourless and non-chromated zinc-aluminum alloy deposits was observed. It was found that rest potential was slightly increased with the increase in the concentration of aluminum chloride, only in the case of golden chromating. The rest potential of colourless chromated zinc-aluminum deposits on mild steel were observed to have no correlation with aluminum chloride concentration. The abrasion resistance of colourless chromating was better than golden chromating.